Improving Online Product Marketing Learning Achievement in Creative Products and Entrepreneurship Subjects for Class XII Accounting Students Using Problem Based Learning Learning Models at SMKN 1 Bunguran Barat - Rozi Gusrianto (UMSU, 2021)
This research was carried out at SMK N 1 Bunguran Barat in Class XII Accounting, where the ability of students for online product marketing material in the eyes of each product course was low. The purpose of this classroom action research research is to find out whether the Problem Based Learning method can improve student learning achievement. The data collection method is daily practice exercises followed by a learning achievement test. The data analysis method is descriptive. The results obtained from this study are the group assignment method with the Problem Based Learning Model which can improve the learning achievement of students. This is evident from the results obtained initially reaching an average value of 48.75, in the first cycle the average value was 67.50 and in the second cycle the average value was 73.88. The conclusion obtained from this study is that the Problem Based Learning model through independent and group assignment techniques can improve learning achievement